Functions and Specifics of Soviet Photography in 1940–1953 - Matulytė, Margarita (Genocidas ir rezistencija, 2003)
The article reveals specifics of the Soviet photography, explains methods and forms of propaganda work, and discusses the major public spheres where the Soviet photography functioned: mass media and museology, and takes a more accurate look on how photo documents were used in Soviet security structures. Talking about the fates of photographers and their activities in 1940–1953, a general situation has been defined clarifying the nature and motivation for their work. The article also gives a deeper analysis of unpublished facts and autobiographical documents of the very photographers. There was also an attempt to examine the mechanisms, volume and influence of the photo documents spread in the Soviet society, to reveal the aim for sovietisation of the photography art, estimate the peculiarities of the photo archive of the Soviet citizens.
Keywords: Soviet art; Soviet photography; cenzorship; propaganda